Long term complications in single and dual chamber pacing are influenced by surgical experience and patient morbidity. Issue 4 (16th March 2005) - Eberhardt, F; Bode, F; Bonnemeier, H; Boguschewski, F; Schlei, M; Peters, W; Wiegand, U K H
Abstract : Objective: To determine how short and long term complication rates after pacemaker implantation are influenced by patient morbidity, operator experience, and choice of pacing system. Design: Retrospective analysis of 1884 patients who received VVI (n  =  610), VDD (n  =  371), or DDD devices (n  =  903) between 1990 and 2001. Follow up period was 64 (34) months. The influence of age, sex, coronary artery disease, myocardial infarction, reduced left ventricular (LV) function, right ventricular (RV) dilatation, atrial fibrillation, device type, and operator experience on operation time and complication rate were analysed. Results: Operation time was prolonged in patients with coronary artery disease, inferior myocardial infarction, reduced LV function, and RV dilatation. Implantation of DDD pacemakers prolonged operation time, particularly among operators with a low or medium level of experience. The overall complication rate was 4.5%. Sixty seven per cent of these complications occurred within the first three months. Complication rate was increased by age, reduced LV function, and RV dilatation. Implantation of DDD systems led to a higher complication rate (6.3%) than implantation of VVI (2.6%) or VDD pacemakers (3.2%). These differences were present only among operators with a low or medium level of experience. Conclusions: Operation time and complication rate increased with age, impaired LV function, and RV dilatation. Complication rates were higher with DDD than with VVI or VDD implantation and were excessive among inexperienced but not experienced operators.